Using Linked Federal and State Data to Study the Adequacy of Workers’ Compensation Benefits - Seabury, Seth A. (Am J Ind Med, 2014)
BACKGROUND: We combined federal and state administrative data to study the long-term earnings losses associated with occupational injuries and assess the adequacy of workers’ compensation benefits. METHODS: We linked state data on workers’ compensation claims from New Mexico for claimants injured from 1994-2000 to federal earnings records from 1987-2007. We estimated earnings losses up to 10 years after injury and computed the fraction of losses replaced by benefits. RESULTS: Workers with lost-time injuries lost an average of 15% of their earnings over the 10 years after injury. On average, workers’ compensation income benefits replaced 16% of these losses. Men and women had similar losses and replacement rates. Workers with minor injuries had lower losses but also had lower replacement rates. CONCLUSION: Earnings losses after an injury are highly persistent, even for comparatively minor injuries. Income benefits replace a smaller fraction of those losses than previously believed.